Comorbid Profile of Tooth Extraction Patients at the Special Dental and Oral Hospital Faculty of Dentistry, Universitas Indonesia Period 2018“2020 - Evy Eida Vitria; Jeanie Cornelia (Dentika: Dental Journal, 2023)
Patients visiting the dentist for treatment may have different comorbidities, which refers to the existence of multiple disorders in an individual during a specific period. These comorbidities consist of both physical and psychological illness, occurring alongside the primary condition of patients, and potentially worsening their overall health condition. The condition adversely affects patients survival and can have an impact on the physiological burden, as well as on treatment options. Therefore, this retrospective descriptive study aimed to determine the distribution and frequency of comorbid diseases in dental extraction patients using secondary data from medical records and at the Special Dental and Oral Hospital (RSKGM) FKG UI from 2018 to 2020. Based on 718 samples of medical records of tooth extraction patients, 341 patients, accounting for 47.5% had comorbid diseases, with a percentage of 61.87% and 38.13% for female and male patients, respectively. The most common comorbid disease occurred in the age group of 21“30 years with a percentage of 38.4%. Furthermore, the most common comorbid disease found in tooth extraction patients was digestive disorders, followed by hypertension, accounting for 56.6% and 23.5%, respectively. Most of the indications for tooth extraction were root gangrene at 32.6%, followed by pulpal gangrene with a percentage of 30.8%. The results of this study indicate that most of the patients with tooth extraction had comorbid diseases and the most frequently found were gastrointestinal disorders and hypertension.